2001
DOI: 10.1177/159101990100700404
|View full text |Cite
|
Sign up to set email alerts
|

Role of Superselective Angiography in the Detection and Endovascular Treatment of Ruptured Occult Arteriovenous Malformations

Abstract: Three cases of occult micro-arteriovenous malformations not identified by cerebral angiography or other imaging modalities were detected by superselective angiography. The first case had a small intracerebral hemorrhage in the superior colliculus, the second had a perimesencephalic subarachnoid hemorrhage, and the third presented with intracerebral hemorrhage combined with massive intraventricular hematoma. While repeated selective cerebral angiography (four-vessel study) was negative, superselective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…4 In the present study 2 lesions were only demonstrated angiographically 3 and 6 months postbleeding. Superselective angiography 2,13,18 increases the diagnostic yield, allowing a definite diagnosis and permits better evaluation of the anatomical location and the angioarchitecture of the lesion. Willinsky and colleagues 18 described 5 patients with micro-AVMs who underwent superselective angiography.…”
Section: Discussionmentioning
confidence: 99%
“…4 In the present study 2 lesions were only demonstrated angiographically 3 and 6 months postbleeding. Superselective angiography 2,13,18 increases the diagnostic yield, allowing a definite diagnosis and permits better evaluation of the anatomical location and the angioarchitecture of the lesion. Willinsky and colleagues 18 described 5 patients with micro-AVMs who underwent superselective angiography.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been rare cases diagnosed only by the pathologic examinations after the surgical acquisition of the specimen, with no radiological evidences of the AVMs. 2,5,6,20,22,24,26,27,32) In the pre-MR era when lesions were evaluated with brain CT and DSA alone, such rare cases were called angiographically occult AVMs. 22) Crawford and Russell et al firstly used the term "cryptic" for small angiomatous malformation that could not be localized due to hematoma and small size.…”
Section: Discussionmentioning
confidence: 99%
“…Superselectivity in cerebral angiography has been implemented in our institution for 27 years and is routinely used as an additional diagnostic tool in selected cases. Its diagnostic yield and safety for children and adults has been proved for almost every aspect of cerebrovascular pathology [15][16][17][18][19][20][21][22] . Other groups have also reported on the role and safety of superselective catheterization for the endovascular approach to small calibre vessels with aneurysms, the evaluation of newly formed collaterals after revascularization procedures in children with moyamoya, even after catheterization of the vasospasm-prone middle meningeal and temporal arteries [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%